A theoretical integration of the social skill deficit vulnerability model and social determination theory to examine young adult loneliness - Curran, Timothy; Elwood, Rebecca E. (Frontiers in Communication, 2024)
Loneliness is an urgent public health crisis that is associated with deleterious outcomes such as early mortality and mental health issues. This study investigates how interpersonal communication apprehension is linked to loneliness through the basic psychological human needs (Ryan, 1995). Guided by a theoretical integration of the social skill deficit vulnerability model and basic psychological needs theory, we examined survey reports from 406 participants.The results showed that interpersonal communication apprehension was related to all three basic psychological needs. Moreover, competence significantly mediated the link between apprehension and loneliness. We discuss the theoretical and practical implications of these findings.